Comparative analysis of the total factor of productivity changes for banks of Visegrad group for the period 2009-2013 - Pilyayskyy, Anatoliy; Aaronson, William; Černohorská, Liběna (Foundation of the Cracow University of Economics, 2017)
The article studies the total factor of productivity (TFP) changes differences between banks of the Visegrad group (V4) (Czech Republic, Poland, Hungary and Slovak) during the period 2009-2013. The analysis of TFP changes has been done to determine the productivity changes of the selected banking sector in Visegrad group countries during and after the financial crisis. We found that (TFP) changes across all countries were relatively stable in 3 of the 4 observation periods. Nevertheless, there was a substantial decline in TFP in 2011-12. Examination of the trends for each of the countries showed that Hungary overly influenced the sample mean. The TFP remained stable during this period for all Poland and the Czech Republic, declined slightly for Slovakia, but declined precipitously for Hungary in 2011-12.
Komparativní analýza změn celkové produktivity bank ve Visegrádských zemích v letech 2009 – 2013
Keywords: Performance of Banks; Visegrad Group; Technical Efficiency; Total Factor of Productivity Changes; výkonnost bank; Visegrádská skupina; celková produktivita; technická výkonnost